Insights into the Novel Therapeutics and Vaccines against Herpes Simplex Virus - Shiza Malik; Ranjit Sah; Omar Ahsan; Khalid Muhammad; Yasir Waheed (Vaccines, 2023)
Herpes simplex virus (HSV) is a great concern of the global health community due to its linked infection of inconspicuous nature and resultant serious medical consequences. Seropositive patients may develop ocular disease or genital herpes as characteristic infectious outcomes. Moreover, the infectious nature of HSV is so complex that the available therapeutic options have been modified in certain ways to cure it. However, no permanent and highly effective cure has been discovered. This review generates insights into the available prophylactic and therapeutic interventions against HSV. A methodological research approach is used for study design and data complication. Only the latest data from publications are acquired to shed light on updated therapeutic approaches. These studies indicate that the current antiviral therapeutics can suppress the symptoms and control viral transmission up to a certain level, but cannot eradicate the natural HSV infection and latency outcomes. Most trials that have entered the clinical phase are made part of this review to understand what is new within the field. Some vaccination approaches are also discussed. Moreover, some novel therapeutic options that are currently in research annals are given due consideration for future development. The data can enable the scientific community to direct their efforts to fill the gaps that remain unfilled in terms of therapies for HSV. The need is to integrate scientific efforts to produce a proper cure against HSV to control the virus spread, resistance, and mutation in future disease management.